Anatomía de las especies cubanas del género Thelypteris Schmidel, subgénero Cyclosorus Morton - Zavaro Pérez, Carlos Alberto (1995)
Anatomic patterns of root, petiole, rachis and blade are offered and discussed in the Cuban species of the genus Thelypteris, subgenus Cyclosorus.